Plasma proteins associated with cardiovascular death in patients with chronic coronary heart disease: a retrospective study - Wallentin, Lars; Eriksson, Niclas; Olszowka, Maciej; Grammer, Tanja B.; Hagström, Emil; Held, Claes; Kleber, Marcus E.; Koenig, Wolfgang; März, Winfried; Stewart, Ralph A. H.; White, Harvey D.; Åberg, Mikael; et al. (PLoS medicine, 2021)
Background Circulating biomarkers are associated with the development of coronary heart disease (CHD) and its complications by reflecting pathophysiological pathways and/or organ dysfunction. We explored the associations between 157 cardiovascular (CV) and inflammatory biomarkers and CV death using proximity extension assays (PEA) in patients with chronic CHD. Methods and findings The derivation cohort consisted of 605 cases with CV death and 2,788 randomly selected non-cases during 3-5 years follow-up included in the STabilization of Atherosclerotic plaque By Initiation of darapLadIb TherapY (STABILITY) trial between 2008 and 2010. The replication cohort consisted of 245 cases and 1,042 non-cases during 12 years follow-up included in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study between 1997 and 2000. Biomarker levels were measured with conventional immunoassays and/or with the OLINK PEA panels CVD I and Inflammation. Associations with CV death were evaluated by Random Survival Forest (RF) and Cox regression analyses. Both cohorts had the same median age (65 years) and 20% smokers, while there were slight differences in male sex (82% and 76%), hypertension (70% and 78%), and diabetes (39% and 30%) in the respective STABILITY and LURIC cohorts. The analyses identified 18 biomarkers with confirmed independent association with CV death by Boruta analyses and statistical significance (all p < 0.0001) by Cox regression when adjusted for clinical characteristics in both cohorts. Most prognostic information was carried by N-terminal prohormone of brain natriuretic peptide (NTproBNP), hazard ratio (HR for 1 standard deviation [SD] increase of the log scale of the distribution of the biomarker in the replication cohort) 2.079 (95% confidence interval [CI] 1.799-2.402), and high-sensitivity troponin T (cTnT-hs) HR 1.715 (95% CI 1.491-1.973). The other proteins with independent associations were growth differentiation factor 15 (GDF-15) HR 1.728 (95% CI 1.527-1.955), transmembrane immunoglobulin and mucin domain protein (TIM-1) HR 1.555 (95% CI 1.362-1.775), renin HR 1.501 (95% CI 1.305-1.727), osteoprotegerin (OPG) HR 1.488 (95% CI 1.297-1.708), soluble suppression of tumorigenesis 2 protein (sST2) HR 1.478 (95% CI 1.307-1.672), cystatin-C (Cys-C) HR 1.370 (95% CI 1.243-1.510), tumor necrosis factor-related apoptosis-inducing ligand receptor 2 (TRAIL-R2) HR 1.205 (95% CI 1.131-1.285), carbohydrate antigen 125 (CA-125) HR 1.347 (95% CI 1.226-1.479), brain natriuretic peptide (BNP) HR 1.399 (95% CI 1.255-1.561), interleukin 6 (IL-6) HR 1.478 (95% CI 1.316-1.659), hepatocyte growth factor (HGF) HR 1.259 (95% CI 1.134-1.396), spondin-1 HR 1.295 (95% CI 1.156-1.450), fibroblast growth factor 23 (FGF-23) HR 1.349 (95% CI 1.237-1.472), chitinase-3 like protein 1 (CHI3L1) HR 1.284 (95% CI 1.129-1.461), tumor necrosis factor receptor 1 (TNF-R1) HR 1.486 (95% CI 1.307-1.689), and adrenomedullin (AM) HR 1.750 (95% CI 1.490-2.056). The study is limited by the differences in design, size, and length of follow-up of the 2 studies and the lack of results from coronary angiograms and follow-up of nonfatal events. Conclusions Profiles of levels of multiple plasma proteins might be useful for the identification of different pathophysiological pathways associated with an increased risk of CV death in patients with chronic CHD. Trial registration ClinicalTrials.gov NCT00799903.